VD_FINDINFO Arrêt / 2023 / 676 vom 26. September 2023 - VD Tribunal cantonal (2023)
VIRUSMALADIE, PERTE DE TRAVAIL, RÉDUCTION DE L'HORAIRE DE TRAVAIL | 31 LACI, 32 LACI, 33 al. 1 let. a LACI, 33 al. 1 let. b LACI